The Role of Gut Microbiota in Modulating Cancer Therapy Efficacy - Mostafa A. Madkour; Rawan A. Altaf; Zeinab S. Sayed; Noha S. Yasen; Hanan A. Elbary; Reem A. Elsayed; Esraa N. Mohamed; Mohamed Toema; Al-Hassan Soliman Wadan; Mohamed H. Nafady; Sanaa A. El-Benhawy (Advanced Gut & Microbiome Research)
Gut microbiota substantially impacts pathogenic and normal immune responses and is associated with common chronic diseases. Moreover, it has a considerable effect on the efficacy of cancer therapy. Variant gut microbiota is linked with immune checkpoint inhibitors, chemo drugs, and radiotherapy resistance. Therefore, a comprehensive interpretation of the interactions between microbiota and cancer therapies is required to encourage researchers to develop new cancer prevention strategies and weaken the consequences of the different cancer therapies. This review discusses the modulating role of gut microbiota that impacts the efficacy of cancer therapies and focuses on its influence on each treatment method, in addition to delivering an overview of the gut microbiota’s role and forming relationships between bacteria, inflammation, and cancer therapies. Highlighting the mechanism of action of probiotics, antibiotics, fecal microbiota transplantation, and prebiotics promotes cancer therapies’ efficacy. Consequently, this makes the gut microbiota essential as a new adjunct augmenting the cancer therapeutic response.